2023
DOI: 10.3390/antib12010005
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Currently Available Antibody Therapy for the Treatment of Coronavirus Disease 2019 (COVID-19)

Abstract: Monoclonal antibodies are a promising treatment for COVID-19. However, the emergence of SARS-CoV-2 variants raised concerns about these therapies’ efficacy and long-term viability. Studies reported several antibodies, that received authorization for COVID-19 treatment, are not effective against new variants or subvariants of SARS-CoV-2, hence their distribution has to be paused. Here, the authors reviewed the status of the currently available monoclonal antibodies for COVID-19 treatment, their potential as a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 98 publications
0
19
0
Order By: Relevance
“…Among the SARS-CoV-2 viral proteins, the spike, envelope, membrane, and nucleocapsid proteins are the main targets of structural protein–based therapeutics for SARS-CoV-2 ( 34–36 ). All 5 of the mAb therapies we evaluated specifically targeted the spike protein ( 37 ). The spike protein mediates attachment of SARS-CoV-2 to the host cell by binding the human angiotensin-converting enzyme 2 receptor through its receptor-binding domain ( 38 ) and is thus a practical target for neutralizing antibodies ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the SARS-CoV-2 viral proteins, the spike, envelope, membrane, and nucleocapsid proteins are the main targets of structural protein–based therapeutics for SARS-CoV-2 ( 34–36 ). All 5 of the mAb therapies we evaluated specifically targeted the spike protein ( 37 ). The spike protein mediates attachment of SARS-CoV-2 to the host cell by binding the human angiotensin-converting enzyme 2 receptor through its receptor-binding domain ( 38 ) and is thus a practical target for neutralizing antibodies ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The acquisition by SARS-CoV-2 of mutations that enable it to evade mAbs will almost certainly continue, thus affecting the utility and longevity of mAbs in managing the ongoing pandemic ( 41 ). Therefore, an mAb that targets the conserved viral epitopes is important for the development of broad-spectrum antibody therapies ( 37 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, patient-derived monoclonal antibodies (mAbs) binding these RBD chains potently neutralize virus cell entry in vitro and protect different animals from viral challenge [17][18][19][20][21] , confirming the crucial role of RBM in engaging the receptor and demonstrating its immunogenicity in vivo. These mAbs are currently in clinical use or in advanced clinical development 22 .…”
Section: Design and Construction Of The Omv-based Vaccinementioning
confidence: 99%
“…Monoclonal antibodies (mAbs) that target the S or RBD proteins have been shown to be useful in treating SARS- CoV-2 infection [13,14]. However, it has been reported that the efficacy of some mAbs against specific variants and subvariants can be variable [15]. The Food and Drug Administration (FDA) has granted emergency use authorization to a number of antibody therapies, generally in the form of a mixed cocktail of antibodies, to better target a broad spectrum of SARS-CoV-2 variants [16].…”
Section: Introductionmentioning
confidence: 99%